Analysis of Milling Performance of High-Entropy Alloys with Different Elemental Ratios Subject to the Assistance of Various Ultrasonic Systems - Lin, Shen-Yung; Chen, Bo-Chun (Applied sciences, 2025)
High-entropy alloys (HEAs) possess multi-element composition and uniform structure, exhibiting superior microstructure and properties compared to traditional alloys. However, the multi-element composition of HEAs results in a complex internal composition configuration with exceptionally high hardness and strength, leading to various machining defects under cutting loading such as poor surface roughness, excessive machining temperature, and cutting tool wear. This study investigates the milling performance of FeCoNiCrMnx HEAs with different elemental ratios subjected to various ultrasonic-assisted milling techniques, aiming to identify the better ultrasonic assisted technique and machining process parameters. The ultrasonic-assisted milling techniques include single-axis ultrasonic, dual-axis ultrasonic, and triple-axis ultrasonic. The side milling experiments were performed on three different elemental ratios of HEAs, e.g., FeCoNiCrMn0.1, FeCoNiCrMn0.5, and FeCoNiCrMn1.0 workpieces. The study is divided into two phases. Each alloy workpiece undergoes side-milling experiments using two designated combinations of feed rate and radial cutting depth subjected to various ultrasonic-assisted milling techniques in the first phase. The purpose is to identify which ultrasonic-assisted milling technique may provide the better surface quality for different elemental ratios and to analyze the performance of various cutting condition combinations in terms of surface roughness and cutting tool wear. Based on the results of the first phase, the better ultrasonic-assisted milling technique is selected and an L9 Taguchi orthogonal array is then employed for process parameter planning, by varying spindle speed, feed rate, and radial cutting depth to investigate the effects of different process parameter combinations on machining performance of HEAs with different elemental ratios. The results show that ultrasonic assistance significantly improves the cutting performance in aspects such as reduction of cutting force and cutting tool wear, and the surface quality of alloys with high Mn content. In the first phase experiment, as compared to milling without assistance, the surface roughness may be reduced up to approximately 17.86% by single-axis ultrasonic-assisted milling using the Set 1 process parameters for different elemental ratios, while it achieves up to approximately 34.4% in surface roughness and approximately 17.68% in cutting tool wear using the Set 2 process parameters. The results from the second phase of experiments reveal a more moderate fluctuation of surface roughness and an approximate reduction from 22.03% to 314.27%, with an approximate reduction from 3.64% to 54.45% in cutting force, and an approximate reduction from 0.58% to 94.77% in cutting tool wear for the higher Mn content alloy in contrast to the lower Mn content one. The integrity of the surface morphology is significantly improved as the elemental ratio, x, is increased to 1.0, resulting in a reduction in machined surface deformation and more consistent milling marks on the machined surface, which indicates a higher stable state of machining quality.